Electron-beam lithography of cinnamate polythiophene films: conductive nanorods for electronic applications - Bojanowski, Maximilian; Huck, Christian; Veith, Lisa; Strunk, Karl-Philipp; Bäuerle, Rainer; Melzer, Christian; Freudenberg, Jan; Wacker, Irene; Schröder, Rasmus R.; Tegeder, Petra; Bunz, Uwe H. F. (Chemical science, 2022)
We report the electron-beam induced crosslinking of cinnamate-substituted polythiophene proceeding via excited state [2+2]-cycloaddition. Network formation in thin films is evidenced by infrared spectroscopy and film retention experiments. For the polymer studied herin, the electron-stimulated process appears to be superior to photo (UV)-induced crosslinking as it leads to less degradation. Electron beam lithography (EBL) patterns cinnamate-substituted polythiophene thin films on the nanoscale with a resolution of around 100 nm. As a proof of concept, we fabricated nanoscale organic transistors using doped and cross-linked P3ZT as contact fingers in thin film transistors.